Ekspektasi vs Realita Guru: Analisis Kinerja, Pengalaman Mengajar, dan Pendidikan dalam Profesionalisme Guru - Marsasanda Andarin; Hana Salsabila Putri (Program Studi Magister Manajemen Pendidikan, 2025)
Teachers are the main component of the education system and play an important role in improving the quality of learning and developing qualified human resources. Ideally, teachers are expected to possess professional competence, extensive teaching experience, and adequate educational backgrounds. However, the reality in the field shows various challenges that create a gap between expectations and educational practices. This article aims to describe the gap between teachers’ expectations and realities in terms of performance, teaching experience, and educational background. This study employed a literature review method with a qualitative descriptive approach through the analysis of books, journals, and previous research related to teacher professionalism. The findings indicate that teachers still face various obstacles, such as high administrative workloads, limited facilities and access to technology, stagnation in teaching practices, and gaps between educational theory and classroom implementation. In addition, teaching experience and formal education do not fully guarantee improvements in learning quality without continuous professional development and institutional support. Therefore, systemic support is needed in the form of bureaucratic simplification, enhancement of professional training, and the provision of adequate learning facilities to sustainably improve teacher professionalism.